A history of God the 4000-year quest of Judaism, Christianity, and Islam - Armstrong, Karen (New York Ballantine Books, 1994)
Why does God exist? How have the three dominant monotheistic religions - Judaism, Christianity and Islam - shaped and altered the conception of God? How have these religions influenced each other? Karen Armstrong traces the history of how men and women have perceived and experienced God from the time of Abraham to the present. The epic story beings with the Jews' gradual transformation of pagan idol worship in Babylon into true monotheism, a concept previously unknown in the world. Christianity and Islam both rose on the foundation of this revolutionary idea, but these religions refashioned "the One God" to suit the social and political needs of their followers. From classical philosophy and medieval mysticism to the Reformation, the Enlightenment and the modern age of skepticism, Armstrong distills the intellectual history of monotheism into one readable volume.
"Originally published in Great Britain by William Heinemann Ltd., London"--Title page verso.
Keywords: God -- Comparative studies. God -- Biblical teaching. God -- History of doctrines. God (Islam) -- History of doctrines. God (Judaism) -- History of doctrines. Judaism -- Doctrines -- History. Islam -- Doctrines -- History. God. Islam -- Doctrines. Judaism -- Doctrines. God -- Christianity. God -- Judaism. God -- Islam